RANCANG BANGUN RANGKA MESIN ROASTING KOPI OTOMATIS KAPASITAS 5 KG: DESIGN AND CONSTRUCTION OF AUTOMATIC COFFEE ROASTING MACHINE CAPACITY 5 KG - Arda, Arda Arya Pratama (Jurnal Teknik Mesin, 2022)
Coffee processing roasting process technology is still limited, with processing using traditional roasting methods. This takes a long time and the temperature cannot be regulated as required. Therefore, roasting machine innovation is required to create a 5 kg capacity automatic coffee roasting machine. The innovative roasting machine was designed with the quality of the engine frame in mind.The study prepared in this report aims to complete the steps of the process of designing, calculating and testing the framework of a 5 kg capacity coffee roaster. The design, calculation and analysis of the frame system examines the calculation of the material, calculation of the load, balance of labor, stress analysis, displacement, safety of the factors on the heating chamber frame, the top cover frame, the stepping motor frame, the calculation of welded joints. Based on the results and discussion, the frame material uses ASTM A36 steel with a square hollow stock profile measuring (30 × 30 × 1.2) mm. Welding is done by welding the butt joint, T joint and corner joint. The permissible stress value of the material is 176.72 N/mm2. The load on the heating chamber is 3,920 N/mm2, on the upper frame cover 1,263 N/mm2 and on the stepper motor 4,947 N/mm2. The stress value for the frame is 47N/mm2 (Mpa), the displacement value is 0.41mm, the safety factor value is 8.